More than Merkle : a history of the best and most exciting baseball season in human history - Anderson, David W. (David Wallace), 1948- (University of Nebraska Press, 2000)
"The arrival of a new baseball season serves to rekindle an old question: Which was the most exciting season ever played? In a book called More Than Merkle, David W. Anderson comes up with an answer that will startle many fans: the season of 1908. Just to make things perfectly clear, he subtitles his opus 'A History of the Best and Most Exciting Baseball Season in Human History.' Of course, the centerpiece is Fred 'Bonehead' Merkle, whose 'boner' of not running from first to second base while the winning run was scoring cost the New York Giants a pennant. Both leagues had close races that year, and the author covers them in exuberant detail. He also focuses on such star players as Christy Mathewson, Three-Finger Brown and Johnny Evers, not to mention more obscure figures, such as a pitcher with the fascinating name of Orval Overall, who won two games for the Chicago Cubs in the World Series (their last World Championship). Baseball antiquarians will relish the book."--Parade